Baby Kit for Disaster sebagai Inovasi Kesiapsiagaan Ibu dalam Menghadapi Bencana di Kawasan Rawan Bencana - Anggraini Khodijaturrohmah; Andi Hayyun Abiddin; Agus Khoirul Anam (Universitas Malahayati Lampung, 2026)
ABSTRACT Disaster situations place vulnerable groups—such as pregnant and breastfeeding mothers, infants, children, the elderly, persons with disabilities, and individuals with chronic illnesses—as priority populations in rescue and health service efforts. Children are often overlooked during the preparedness phase, indicated by limited resource availability, risk of separation from parents, increased health problems, and limited ability to protect themselves. Previous research identified the lack of research-based disaster emergency bags specifically designed to meet infant and child needs. This study aims to develop a Baby Kit for Disaster as an innovation to enhance family preparedness in disaster-prone areas. A Research and Development (RD) design using the ADDIE model was employed, including needs analysis, product design, and development through production, expert validation, and revision. Inclusion criteria included mothers with infants aged 0–24 months living in disaster-prone areas of Blitar City, while exclusion criteria included mothers with cognitive impairment or unwillingness to participate. The study was conducted at Lembaga Pendidikan Jiwa, Blitar City, in September 2025. Needs analysis indicated the necessity for a practical, safe, accessible, and functional emergency kit supporting infant care, including food, clean water, breastfeeding needs, and primary health items. The Baby Kit for Disaster is expected to serve as an effective solution to strengthen family preparedness and ensure infant safety and health during disasters. Keywords: Disaster Preparedness, Baby Kit for Disaster, Vulnerable Groups, RD ADDIE. ABSTRAK Situasi bencana menempatkan kelompok rentan seperti ibu hamil dan menyusui, bayi, anak-anak, lansia, penyandang disabilitas, dan individu dengan penyakit kronis sebagai prioritas utama dalam proses penyelamatan dan pelayanan kesehatan. Anak-anak sering terabaikan dalam tahap kesiapsiagaan, ditandai dengan kurangnya sumber daya, risiko terpisah dari orang tua, serta keterbatasan kemampuan melindungi diri. Penelitian sebelumnya menunjukkan masih minimnya pengembangan tas siaga bencana berbasis riset untuk kebutuhan khusus bayi dan anak. Penelitian ini bertujuan mengembangkan Baby Kit for Disaster sebagai inovasi kesiapsiagaan keluarga dalam menghadapi bencana . Metode yang digunakan adalah Research Development (RD) dengan model ADDIE, mencakup analisis kebutuhan, perancangan desain, dan pengembangan produk melalui proses pembuatan, validasi ahli, dan revisi. Kriteria inklusi meliputi ibu dengan bayi usia 0–24 bulan yang berdomisili di kawasan rawan bencana Kota Blitar, sedangkan eksklusi mencakup ibu dengan gangguan kognitif atau menolak berpartisipasi. Penelitian dilakukan di Lembaga Pendidikan Jiwa Kota Blitar pada September 2025. Analisis kebutuhan menunjukkan perlunya perlengkapan darurat bayi yang praktis, aman, tepat guna, dan mudah dijangkau, khususnya terkait makanan, air, perawatan bayi, dan kebutuhan ASI. Produk Baby Kit for Disaster diharapkan menjadi solusi efektif dalam meningkatkan kesiapsiagaan keluarga untuk melindungi kesehatan dan keselamatan bayi pada situasi bencana Kata Kunci: kesiapsiagaan Bencana, Baby Kit for Disaster, RD ADDIE.